The Effectiveness Of Oral Appliance In Comparison With Continuous Positive Airway Pressure In The Treatment Of Obstructive Sleep Apnoea: A Randomised Clinical Trial - Elsherbiny, Momen Zaky Elsayed (2016)
A parallel design randomised controlled trial was conducted at the Advanced Medical and Dental Institute (AMDI) Universiti Sains Malaysia (USM) to determine the effectiveness of oral appliances (OA) in comparison to the continuous positive airway pressure (CPAP) in the treatment of obstructive sleep apnoea. Patients referred from the Ear, Nose and Throat clinic were screened for eligibility to participate in the trial. After considering all the inclusion and exclusion criteria, 40 patients were recruited and were randomised by an online randomization software available on (www.randomization.com) which was used to produce a randomization plan.